Influencia de la gestión cultural del museo de sitio y complejo Arqueológico de Túcume en el fortalecimiento de la identidad cultural de la población local - Quiroz Hernández, Zoila Analy (2018)
ABSTRACT The present investigation entitled: Influence of the Cultural Management of the Site Museum and Archaeological Complex of Túcume in the strengthening of the Cultural Identity of the Local Population, Its purpose is to determine the influence of the Cultural Management of the Túcume Site Museum in strengthening the cultural identity of children, youth and adults; allowing to verify through a structured process of primary and secondary information collection the research hypothesis and making use of analytical-synthetic and ethnographic methods; who favored both in the field and cabinet stage: the collection, processing, and analysis of the exposed data, the survey technique applied to the children, youth and adults of the district to determine characteristics associated with their cultural identity, the interview that facilitated the obtaining of information on the part of the managers directed to the Director of the Museum of Site of Túcume the Arql ° Bernarda Delgado Elías, knowing his main contributions in relation to the cultural management and to the settlers of the district of Túcume; The instruments used were interview guides, survey questionnaire and observation guides. The document presents the results and discussion of 3 research variables; children whose main objective is to identify the degree of knowledge they have regarding their culture as well as the role they play as part of the cultural management of the Túcume Site Museum. In the same way, young people whose objective is to determine the forms of participation of this segment of the population as well as the interest associated with the professional vocation for tourism and culture. Finally adults, allowing them to identify the signs of continuity expressed in the cuisine, crafts and folklore of their people, making possible the generation of local enterprises. The cultural management that has been carried out both in the Museum and in the Archaeological Complex of Túcume shows the synergy of efforts between the cultural managers and the community that houses them, oriented not only to the conservation and promotion of the monument and museum, but also also its implication has been such, that it is possible to demonstrate the leading role played by children, youth and adults as part of the management, actively participating in the activities called by the managers, within them the workshop of craftsmen, folk dances, radio station radial; whose positive impact today is seen in the change of attitude of the community and in the more open and proud use of the icons and symbols most representative of the local culture; In the case of adults, there is also evidence of the initiative of local enterprises expressed in craft stalls, restaurants where typical food is sold, as well as accommodation service providers.